"Phossy Jaw" and "Bis-phossy Jaw" of the 19th and the 21st Centuries: The Diuturnity of John Walker and the Friction Match. Issue 3 (September 2015) - Pollock, Richard A.; Brown, Ted W.; Rubin, David M.
Some 200 years ago, workers developed gingivitis, periodontal disease, alveolar crest bone sequestra, and draining fistulae after exposure to phosphorous fumes and phosphorous paste in the manufacture of the friction match. Many also suffered loss of teeth and pathologic fracture of the mandible. Known as "phossy jaw, " the constellation rather abruptly vanished following the International Berne Convention of 1906. Today, "bis-phossy jaw" (bisphosphonate-induced osteonecrosis of the jaw) has surfaced with pathologic fractures and other features common to its predecessor, "phossy jaw." This modern equivalent is reported with ever-increasing frequency and is presented here in the format of a brief historical review and a case report that includes segmental en bloc extirpation of necrotic mandible and pain-free salvage. Computerized imagery and three-dimensional printing technology were successfully chosen to create and apply a custom titanium bone plate, without free-tissue transfer.